Dietary and biological assessment of omega-3 status in university rugby football players: a case-control study - Fujibayashi, M.; Nirengi, S.; Segawa, T.; Furuno, S.; Sakane, N. (Asian Journal of Sports Medicine, 2024)
Background:Omega-3 fatty acid supplementation has been shown to help maintain muscle function and reduce muscle soreness after exercise-induced muscle damage. However, the relationship between the dietary and biological status of omega-3 fatty acids in rugby players remains unclear.